2018
DOI: 10.1093/pasj/psx133
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on the fine structure and dynamics of a solar jet. II. Energy release process revealed by spectral analysis

Abstract: We report a solar jet phenomenon associated with the C5.4 class flare on 2014 November 11. The data of jet was provided by Solar Dynamics Observatory (SDO), X-Ray Telescope (XRT) aboard Hinode, Interface Region Imaging Spectrograph (IRIS) and Domeless Solar Telescope (DST) at Hida Observatory, Kyoto University. These plentiful data enabled us to present this series of papers to discuss the entire processes of the observed phenomena including the energy storage, event trigger, and energy release. In this paper,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Subarcsecond plasmoids were detected by the IRIS, whose average size is about 0.57 Mm, and their ejecting speed ranges from 10 to 220 km s −1 [135]. Besides the observation of plasmoids in straight anemone jets [81,[136][137][138][139], they were also observed in two-sided-loop jets [44] (figure 4). Analysis results indicated that plasmoids observed in different types of jets were similar, and they were thought to be created by magnetic reconnection as a result of the tearing instability of the current sheets.…”
Section: (Ii) Plasmoidmentioning
confidence: 97%
“…Subarcsecond plasmoids were detected by the IRIS, whose average size is about 0.57 Mm, and their ejecting speed ranges from 10 to 220 km s −1 [135]. Besides the observation of plasmoids in straight anemone jets [81,[136][137][138][139], they were also observed in two-sided-loop jets [44] (figure 4). Analysis results indicated that plasmoids observed in different types of jets were similar, and they were thought to be created by magnetic reconnection as a result of the tearing instability of the current sheets.…”
Section: (Ii) Plasmoidmentioning
confidence: 97%
“…Subarcsecond plasmoids were detected by the IRIS, whose average size is about 0.57 Mm, and their ejecting speed ranges from 10 to 220 km s −1 [135]. Besides the observation of plasmoids in straight anemone jets [81,[136][137][138][139], they were also observed in two-sided-loop jets [43] (see Figure 4). Analysis results indicated that plasmoids observed in different types of jets were similar, and they were thought to be created by magnetic reconnection as a result of tearing instability of the current sheets.…”
Section: (Ii) Plasmoidmentioning
confidence: 95%
“…To compute the LOS velocity and the micro-turbulence inside a filament, we utilised a cloud model first proposed by Beckers (1964). Assuming that (1) the source function is constant along the wavelengths and (2) along the LOS direction and that (3) the line absorption coefficient is a Gaussian shape, this model enables us to determine four physical parameters of the plasma cloud, the source function, the Doppler width, the Doppler shift, and the optical depth (Morimoto & Kurokawa 2003a,b;Morimoto et al 2010;Cabezas et al 2017;Sakaue et al 2018;Seki et al 2017Seki et al , 2019. The LOS velocity (v los ) and the micro-turbulence (ξ) at each pixel were calculated from the Doppler shift (∆λ S ) and the Doppler width (∆λ D ), respectively, based on the equations below (Morimoto & Kurokawa 2003a);…”
Section: Cloud Modelmentioning
confidence: 99%